Die opname van ‘n Jobgedig in enkele eietydse gedigte - Vos, Casparus Johannes Adam 1945- (2010)
The reception of a Job poem in some contemporary poems This article investigates the intertextual influence of an ancient poem on a few modern-day poems. Other literary creations on which ancient poems have left their mark also come to the fore. The ancient poem under discussion here is a Job poem. This study reveals the remarkable creative influence that Job has exerted on literature. In Afrikaans poetry, a range of poets have concerned themselves with Job in their work. This article explores one such unpublished Afrikaans poem and an English translation thereof in order to point out how contemporary and relevant the Job poem really is.
Keywords: Job; antieke teks; eietyds; gedig; opname